Parents' Weekend robot race competition in Anderson Hall. Photo 029 - Loeb, Brian (Tufts Archival Research Center, 2008)
Parents' Weekend robot race competition in Anderson Hall. Students on four teams compete to build four different robots that perform four different tasks.